Effects of air-entraining agent and polypropylene fiber on the mechanical properties, autogenous shrinkage, and fracture properties of fully recycled aggregate concrete - Ding, Dong; Zhang, Lijuan; Zhao, Jun; Li, Changbin; Wang, Zhi (Frontiers in Materials, 2022)
The effects of air-entraining agent (AEA) and polypropylene fiber (PPF) on the autogenous shrinkage and fracture properties of fully recycled aggregate concrete (FRAC) are studied to obtain FRAC with low density, low autogenous shrinkage, and superior fracture properties. Six groups of FRAC with different AEA (0, 5%, 10%) and PPF (0, 1.2 kg/m3) contents were prepared for test. The results illustrate that AEA can slightly reduce density but that it has an adverse effect on the strength and fracture properties of FRAC. The incorporation of PPFs can reduce the adverse effect of AEA on compressive strength and splitting tensile strength, but it will increase the adverse effect on fracture properties. Furthermore, the addition of PPFs alone will significantly reduce compressive strength and splitting tensile strength, whereas flexural strength and fracture properties are increased. The addition of AEA can improve the adverse effect of PPFs on compressive strength and splitting tensile strength, but flexural strength and fracture properties will decrease rather than increase. The addition of 10% AEA can greatly reduce autogenous shrinkage, and 5% AEA can reduce autogenous shrinkage at an early age. Incorporating PPFs can further reduce autogenous shrinkage. The study mainly examines the effects of AEA and PPF on the autogenous shrinkage of FRAC, and provides some new ideas for producing high-performance FRAC. At the same time, the cooperative effect of AEA and PPF on the properties of FRAC is also studied.